2020
DOI: 10.1097/aln.0000000000003522
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood General Anesthesia and Neurodevelopmental Outcomes in the Avon Longitudinal Study of Parents and Children Birth Cohort

Abstract: Background Most common anesthetic agents have been implicated in causing neurodegeneration in the developing animal brain, leading to warnings regarding their use in children. The hypothesis of this study was that exposure to general anesthesia and surgery before 4 yr would associate with adverse neurodevelopmental outcomes at age 7 to 16 yr. Methods This cohort study comprised 13,433 children enrolled in the Avon Longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 50 publications
0
48
0
Order By: Relevance
“…11,12 Recent findings from large-cohort and population-based studies have been conflicting, with some showing developmental delays after anesthetic exposure prior to age 2 years 13,14 and others concluding no impact of a single exposure before age 3 to 4 years on adverse behavior or learning outcomes in later life. 15,16…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Recent findings from large-cohort and population-based studies have been conflicting, with some showing developmental delays after anesthetic exposure prior to age 2 years 13,14 and others concluding no impact of a single exposure before age 3 to 4 years on adverse behavior or learning outcomes in later life. 15,16…”
Section: Discussionmentioning
confidence: 99%
“…The major comorbidities justifying exclusion for each study are described in eTable 5 in the Supplement and include congenital heart disease, extreme prematurity, or medulloblastoma. A further 16 studies were excluded for using cohorts that overlapped with other studies or not reporting outcome scores that could be evaluated (eTable 6 in the Supplement ), and 8 studies were excluded for not reporting overall domain scores, leaving 31 studies 27 , 31 , 33 , 35 , 36 , 40 , 45 , 48 , 56 , 60 , 61 , 63 , 64 , 72 , 76 , 79 , 82 , 87 , 88 , 90 , 91 , 95 , 102 , 103 , 104 , 105 , 107 , 108 , 120 , 122 , 130 contributing data for meta-analysis ( Table ). Owing to a limited number of eligible studies (less than 3 studies) evaluating adaptive behavior, general health and well-being, sensory, and social cognition, these domains could not be evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…The safety of anesthetic exposure in the developing brain of children and infants has attracted significant public attention. Increasing clinical trials have shown that the administration of general anesthesia is associated with deficits in long-term motor coordination and social behavior in children and infants (Ing and Brambrink, 2019;Zaccariello et al, 2019;Feng et al, 2020;Ing et al, 2020;Kobayashi et al, 2020;Walkden et al, 2020). Sevoflurane, the most common anesthetic used in children, is the main object of interest in the study of neurotoxicity of general anesthetics.…”
Section: Introductionmentioning
confidence: 99%